A two-tier multiple-choice diagnostic test to find student misconceptions about the change of matter - Ningroom, Rita Arfi Astuti; Yamtinah, Sri; Riyadi, Riyadi (Journal of Education and Learning (EduLearn), 2025)
There are a lot of very interesting scientific concepts to learn in natural and social science. The initial concepts that the student possesses may contradict the actual concepts, which is what causes misconceptions. Misconceptions are identified using misconception detection test tools. In fact, the development of the use of diagnostic test instruments in Indonesia is still very limited. The objective of the study is to create a diagnostic exam instrument that is two tiers and multiple-choice using certainty of response index (CRI) to identify misunderstandings that students have about changes in matters form in science learning. The research design was research and development (RnD). Development starts with literature studies, design and drafting product drafts, testing product validation with expert validation, and empirical testing. The result analysis showed that the two-tier multiple-choice diagnostic test has a high validity of 0.791. The difficulty level belongs to the moderate category, with a coefficient between 0.2 and 0.8 and a good differential and decaying power. Diagnostic tests are said to be suitable for the detection of misconceptions in science learning in elementary school. The outcome of this study contributes to increasing students' knowledge, understanding, critical thinking, and reducing the level of student misconceptions.